2023
DOI: 10.3389/fphar.2022.1098374
|View full text |Cite
|
Sign up to set email alerts
|

Polypodium leucotomos targets multiple aspects of oral carcinogenesis and it is a potential antitumor phytotherapy against tongue cancer growth

Abstract: Introduction: Oral cancer refers to malignant tumors, of which 90% are squamous cell carcinomas (OSCCs). These malignancies exhibit rapid progression, poor prognosis, and often mutilating therapeutical approaches. The determination of a prophylactic and/or therapeutic antitumor role of the polyphenolic extract Polypodium leucotomos(PL) would be relevant in developing new tools for prevention and treatment.Methods: We aimed to determine the antitumor effect of PL by treating OSCC cell lines with PL metabolites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…The research revealed that within tongue cancer cells, FAM168A, also recognized as tongue cancer resistance-associated protein (TCRP1), has the ability to directly associate with AKT1, influencing the regulation of AKT1/NFκB signaling pathways. Furthermore, the study demonstrated FAM168A’s potential function as a connecting protein, binding both to BCR-ABL1 and AKT1, thereby facilitating downstream signaling pathways in CML 1,8,9…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The research revealed that within tongue cancer cells, FAM168A, also recognized as tongue cancer resistance-associated protein (TCRP1), has the ability to directly associate with AKT1, influencing the regulation of AKT1/NFκB signaling pathways. Furthermore, the study demonstrated FAM168A’s potential function as a connecting protein, binding both to BCR-ABL1 and AKT1, thereby facilitating downstream signaling pathways in CML 1,8,9…”
Section: Introductionmentioning
confidence: 92%
“…The research revealed that within tongue cancer cells, FAM168A, also recognized as tongue cancer resistance-associated protein (TCRP1), has the ability to directly associate with AKT1, influencing the regulation of AKT1/NFκB signaling pathways. Furthermore, the study demonstrated FAM168A's potential function as a connecting protein, binding both to BCR-ABL1 and AKT1, thereby facilitating downstream signaling pathways in CML 1 , 8 , 9 The genes LncKRT16P6 function as promoters in the advancement of tongue squamous cell carcinoma by acting as sponges for miR-3180 and modulating GATAD2A expression. The study findings demonstrate that LncKRT16P6 boosts the growth, movement, and infiltration of tongue squamous cell carcinoma cells through its interaction with miR-3180, thereby regulating the expression of GATAD2A.…”
Section: Introductionmentioning
confidence: 98%
“…Finally, it is worth highlighting the recent findings of Lacerda et al (2023) in the field of oral cancer prevention. Their study demosntrated that PLE has the ability to suppress oral cancer cell growth in vitro in SCC-9, SCC-15, and SCC-25 cell lines, and prevent tumor development in vivo in mice with induced oral carcinogenesis.…”
Section: Oncodermatologymentioning
confidence: 99%
“…A decrease in the expression of Ki67 and PCNA proliferating markers as well as in N-cad (Cdh2), Vim and Twist markers related to migration was observed in tongue tissues. Therefore, PLE may have a beneficial effect on immune and inflammatory responses related to oral tumors and could be a promising natural therapeutic approach for preventing and treating oral cancer due its immunomodulatory activity [32].…”
Section: Oncodermatologymentioning
confidence: 99%